Cultural Differences in Young Adults' Perceptions of the Probability of Future Family Life Events. (September 2017) - Speirs, Calandra; Huang, Vivian; Konnert, Candace
Most young adults are exposed to family caregiving; however, little is known about their perceptions of their future caregiving activities such as the probability of becoming a caregiver for their parents or providing assistance in relocating to a nursing home. This study examined the perceived probability of these events among 182 young adults and the following predictors of their probability ratings: gender, ethnicity, work or volunteer experience, experiences with caregiving and nursing homes, expectations about these transitions, and filial piety. Results indicated that Asian or South Asian participants rated the probability of being a caregiver as significantly higher than Caucasian participants, and the probability of placing a parent in a nursing home as significantly lower. Filial piety was the strongest predictor of the probability of these life events, and it mediated the relationship between ethnicity and probability ratings. These findings indicate the significant role of filial piety in shaping perceptions of future life events.